Giant placental chorioangioma: a rare cause of fetal hydrops. (17th May 2011) - Barros, Andreia; Freitas, Ana Cristina; Cabral, António Jorge; Camacho, Maria Carmo; Costa, Edite; Leitão, Henrique; Nunes, José Luis
Abstract : Giant choriangiomas are rare placental tumours, associated with a high prevalence of pregnancy complications and a poor perinatal outcome. Neonatal consequences include severe microangiopathic haemolytic anaemia, thrombocytopaenia and hydrops. The associated high perinatal death rate (30–40%) has led to a number of prenatal therapeutic interventions with limited success in most cases. The authors present a case of non-immune fetal hydrops caused by a giant chorioangioma, diagnosed at 27 weeks of gestational age. Despite tocolytic therapy, the baby was born prematurely (28 weeks of gestational age) and required transfusion of blood derivatives, intensive phototherapy and exchange transfusion. She had an uncomplicated recovery and was discharged home in the second month of life. The authors emphasise the need to consider chorioangioma as a cause of non-immune fetal hydrops and microangiopathic haemolytic anaemia.